Strengthening Human Resources Management of KORMI Trenggalek Regency in Implementing Community Sports Festivals as an Implementation of the 2045 Fit Indonesia Program - Soleh Fudin, Muhammad; Mareta Sceisarriya, Vega; Susetyo Kusumo Wardhani, Intan; Cahyanto Wibawa, Junian (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Strengthening Human Resources Management in the Indonesian Community Sports Committee (KORMI) Trenggalek Regency is an important step in implementing the Community Sports Festival as part of the implementation of the Indonesia Fit 2045 Program. This festival aims to increase community participation in sports, which is in line with government efforts to create a healthy and active society. This service shows that the development of traditional and recreational sports can increase people's motivation to participate in sports activities, which is the core of the program. One strategy that can be implemented is through training and outreach through community sports management applications packaged in the form of community sports festival activities in traditional games, traditional archery, dance, tera gymnastics and kite flying. This community service shows that understanding and implementing activities through this community sports tournament management application can increase the human resource competency of KORMI Trenggalek Regency partners in developing and providing community sports services to the community, especially implementing easy community sports tournaments with digital applications. With good services from KORMI Trenggalek Regency, it can motivate public awareness in implementing a healthy and fit lifestyle by exercising regularly so that people in Trenggalek Regency are motivated to move towards a Indonesia’s Fit 2045.